Multiple optical path length reflections enhancement based on balloon-type photoacoustic cell for trace gas sensing - Ruiming Wu; Wenjun Ni; Chunyong Yang; Bingze He; Ping Lu; Sixiang Ran; Zhongke Zhao; Perry Ping Shum (Photoacoustics)
A novel balloon-type photoacoustic cell (BTPAC) is proposed to facilitate the detection limitations of acetylene (C2H2) gas achieving ppb level. Here, an ellipsoidal photoacoustic cavity is employed as the platform for gas-light interaction. By strategically directing the excitation source towards the focal point of the ellipsoidal cavity, ensuring its trajectory traverses the focal point upon each reflection from the interior walls. This path increases the gas absorption path length and improves the efficiency of the laser-gas interaction process. Experimental results show that the quality factor of the BTPAC is 224.24 under normal temperature and pressure conditions. Notably, the system maintains a high signal-to-noise ratio even at a C2H2 concentration of 0.1 ppm. Moreover, the minimum detection limit (MDL) and normalized noise equivalent absorption can be calculated to be 3.86 ppb, 6.94·10−10 cm−1·W·Hz−1/2, respectively. Finally, the MDL of the sensor reaches to 0.71 ppb when the integration time reaches 100 s.